Juridicial Review of Legal Protection Victims of Cyber Gender-Based Violence (Case Study of High Court Decision Number 150/PID/2020/PT BDG) - Rinta Ariani, Mahayu; Widodo, Wahyu; Galang Windi Pratama, Toebagus (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2023)
Cyber gender-based violence is a crime that arises due to the development of increasingly sophisticated information technology. In this case, women are more vulnerable to cyber gender-based violence than men. This cyber gender-based violence results in a person's freedom not only being threatened directly in the real world but also in cyberspace, especially the difficulty of identifying the identity of the perpetrator and the victim's digital footprint that has been spread on the internet is difficult to erase. This study aims to determine the legal protection provided by the state to victims of cyber gender-based violence and to determine whether the High Court Decision Number 150/PID/2020/PT BDG has provided protection for victims of cyber gender-based violence. The approach method used in this research is normative juridical research method with qualitative descriptive research specifications. The techniques used to collect data are literature study and documentation study. Based on the research that has been conducted, it is concluded that the protection of victims of cyber gender-based violence is regulated in Law Number 12 of 2012 concerning Criminal Acts of Sexual Violence, which in this law regulates the criminal provisions of the perpetrators and the rights of victims, in this case victims are entitled to restitution, recovery services, and protection, where the fulfillment of these rights is an obligation of the state. And based on the analysis of the decision of the High Court Decision Number 150/PID/2020/PT BDG, it has not provided maximum protection to victims of cyber gender-based violence due to overlapping regulations which cause unclear legal protection for victims of cyber gender violence, especially the existence of rubber articles in the ITE Law which have become a tool to criminalize victims of cyber gender-based violence